Efeito dos fatores climáticos no comportamento dos custos de produção da soja : um estudo nas principais cidades produtoras brasileiras no período de 2005 a 2015 - Oliveira, Karine Gonzaga de (2016)
Soybean is the featured product in Brazilian agribusiness, corresponding for over 49% of the area planted in the country, which corresponds to 30% of world soybean production in the year of 2015. As well as others agricultural products, soybeans are directly affected by environmental conditions, becoming dependent on climate factors, such as temperature, photoperiod and water availability. This study aimed to investigate the behavior of soybean production costs in relation to climatic factors in major producing cities in Brazil from 2005 to 2015. The climate factors analyzed were: insolation, nebulosity, days of precipitation, precipitation total, average temperature, maximum temperature and minimum temperature. Soybean planting costs were examined at all stages of its production (seeding, growing period, reproductive period and harvest). Were performed descriptive analyzes, simple linear correlation and multiple linear regression. The main results showed that, in the period analyzed, the first soybean production stages (growing period) the increase of insolation and de reduction of nebulosity, reduced production costs with temporary labor, seeds, fertilizers, pesticides and depreciation. In growing period, the cost of seeds, fertilizers and periodic maintenance of machinery decreased with daily nebulosity increasing. About water availability, the results indicated that whit the increasing of days of precipitation and of the precipitation total in the growing season, increased production costs with operating machinery, periodic maintenance of machinery, seeds, fertilizers, pesticides and permanent labor. In the reproductive period, the increased of the water availability, decreased the costs of operating machinery and temporary labor. In relation to temperature, the increasing of the maximum temperature, decreased soybean production cost with seeds, in the seeding stage. The increase in average and maximum temperatures, in the reproductive period, have increased the cost of pesticides, perhaps because of the proliferation of parasites.